2002
DOI: 10.1055/s-2002-34494
|View full text |Cite
|
Sign up to set email alerts
|

Friedreich's Ataxia: Idebenone Treatment in Early Stage Patients

Abstract: Cerebellar improvement was notable in mild patients after the first 3 months of therapy. Idebenone treatment at early stages of the disease seems to reduce the progression of cerebellar manifestations. Further blind trials with a greater number of patients and higher doses are needed to fully assess the therapeutic potential of idebenone in Friedreich's ataxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 15 publications
3
77
0
2
Order By: Relevance
“…6 To achieve optimal therapeutic gain, medication strategies for ataxia should be introduced at an early stage. 7 Treatment effects are mostly assessed by surrogate ataxia markers, such as the International Cooperative Ataxia Rating Scale (ICARS). However, ICARS scores in children have not been validated, and it is unclear whether ICARS scores are confounded by other factors such as muscle weakness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 To achieve optimal therapeutic gain, medication strategies for ataxia should be introduced at an early stage. 7 Treatment effects are mostly assessed by surrogate ataxia markers, such as the International Cooperative Ataxia Rating Scale (ICARS). However, ICARS scores in children have not been validated, and it is unclear whether ICARS scores are confounded by other factors such as muscle weakness.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, previous studies in children with FRDA have described improved ICARS scores after experimental treatment with (antioxidative) idebenone medication. 7 However, the 'improved' ICARS scores were interpreted against adult rather than paediatric comparison values. 8 Since ICARS scores in healthy comparison children are likely to 'improve' with age (by maturation), longitudinally improved ICARS scores do not necessarily reflect a positive therapeutic effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, idebenone consistently improved cardiac hypertrophy, which is an important feature of FRDA. Neurological symptoms have not been improved as much as cardiac problems, however higher doses of idebenone especially in younger patients seem to be much more promising for neurological efficacy [76,[85][86][87].…”
Section: Idebenonementioning
confidence: 99%
“…One small, open-label trial in young FA patients found an improvement in overall neurological function that was related to plasma idebenone concentrations. 11 This suggests that treatment may be eff ective if given early in the disease course, and that improvement may be dependent on higher doses of idebenone. This suggestion is supported by the fi nding in two other trials that patients who still had cardiac hypertrophy after treatment with 5 mg/kg idebenone daily subsequently responded when the dose was increased to 10 mg/kg daily.…”
Section: Introductionmentioning
confidence: 99%